Geoindicadores de erosão e acumulação das praias do município de Aracaju - Silva, Manuela Gavazza da (2014)
The coastline of the city of Aracaju in Sergipe/Brazil, extending approximately for 24 km, is limited by the mouth of the Sergipe river in the north and the mouth of Vaza-Barris river in the south. In this work 7 beaches along Aracaju littoral were studied (Mosqueiro, Refúgio, Náufragos, Robalo, Aruana, Atalaia and Artistas), comprising 24 sampling points. The purpose of this dissertation is to outline the erosion and accretion processes of the Aracaju coastal area by using geoindicators of coastal erosion and accretion. The methodology included field campaigns over rainy (Aug/12) and dry (Feb/13) seasons, spatial geoindicators data, human settlement mapping and the development of coastal erosion vulnerability and risk maps using the ArcGIS 9.3.1 program. The Aracaju coastal area is characterized by beaches (ocean and estuary), surrounded by Quaternary sedimentary deposits predominantly from wind (foredune) and, by anthropogenic containment structures against coastal erosion. The erosion process is more effective on the beaches situated in contiguous areas to the mouths of Sergipe River ( Praia dos Artistas ), Vaza-Barris River ( Praia do Mosqueiro ) and in the middle of the beach arc ( Praia do Refúgio and Praia dos Náufragos , in the rainy season). The settlement level is high on the beaches of Praia da Atalaia , Praia dos Artistas , and non-existent on the beach of Praia do Mosqueiro . The coastal erosion vulnerability is high to moderately high on the beaches of Praia dos Artistas , Praia do Mosqueiro , Praia do Refúgio , Praia dos Náufragos , Praia da Aruana and Praia da Atalaia ; and moderately low to low in the other beaches. Depending on the coastal erosion vulnerability index and the human settlement level, the risk of coastal erosion is high on the beach of Praia dos Artistas and moderately high on the beaches of Praia do Refúgio , Praia dos Náufragos and Praia da Atalaia ; and moderately low to low in the other beaches. Although the coast of Aracaju pointed out a high risk just on the beach Praia dos Artistas , attention should be given to areas most vulnerable to erosion due to the intensification of human settlement over recent decades. The results of this study provide baseline information for environmental planning in the area analyzed, especially with regard to the human settlement near to the shoreline.